2014
DOI: 10.1080/07370016.2014.868733
|View full text |Cite
|
Sign up to set email alerts
|

Homeless Women's Experiences of Service Provider Encounters

Abstract: Service providers are gatekeepers to health-sustaining services and resources, although little is known about service encounters from the perspective of homeless women. We conducted in-depth semistructured interviews with 15 homeless women to better understand their experiences of service encounters. Using a phenomenological method, 160 significant statements were extracted from participant transcripts; more positive than negative interactions were reported. The 10 themes that emerged fall along a dehumanizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Given the significant and complex factors involved in homelessness, gatekeepers of health and social services (Biederman & Nichols, 2014) are tasked with meeting the needs of the most vulnerable, helping them navigate larger systems to meet basic necessities, and advocate to access housing and health care. A seminal article found empirical support related to competing priorities (e.g., food, shelter, safety); thus, recommendations include taking into account unmet needs (e.g., clothing, shelter, bathrooms; Gelberg, Gallagher, Andersen, & Koegel, 1997).…”
Section: Changing Landscape: Health and Social Delivery Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the significant and complex factors involved in homelessness, gatekeepers of health and social services (Biederman & Nichols, 2014) are tasked with meeting the needs of the most vulnerable, helping them navigate larger systems to meet basic necessities, and advocate to access housing and health care. A seminal article found empirical support related to competing priorities (e.g., food, shelter, safety); thus, recommendations include taking into account unmet needs (e.g., clothing, shelter, bathrooms; Gelberg, Gallagher, Andersen, & Koegel, 1997).…”
Section: Changing Landscape: Health and Social Delivery Needsmentioning
confidence: 99%
“…Homeless clients have listed respect, actively seeking ways to lessen the power differential, a nonjudgmental approach, and solidarity as the key components of the patient–provider relationship (Oudshoorn, Ward-Griffin, Forchuk, et al, 2013). Another study of provider perceptions revealed that HW described experiences with service providers as neutral, dehumanizing (e.g., unmet expectations, judged, minimized, alienated, powerless), or humanizing (e.g., cared for, trusted, shared past/identity, empowered; Biederman & Nichols, 2014). Others have noted that positive experiences with primary care providers included offering tailored service and having a perceived choice of provider (Chrystal et al, 2015).…”
Section: Changing Landscape: Health and Social Delivery Needsmentioning
confidence: 99%
“…Homeless accommodation services can also work closely with and be a link to community, including referrals to mental health groups, physical health services, and employment services. For instance, Biederman and Nichols () found that women accessing homelessness services most frequently identified the importance of service providers actively conveying care as a means to promote engagement. More generally, there is evidence that homeless accommodation can assist in improved outcomes, such as stable housing, employment, and self‐esteem (Glisson, Thyer, & Fischer, ; Thompson, Pollio, Constantine, Reid, & Nebbitt, ).…”
Section: Group Memberships and Mental Well‐beingmentioning
confidence: 99%
“…Some have indicated a belief that their homeless status affects the quality of the health care they receive or their wait times for care (Nicholas et al, 2016; Wen et al, 2007; Woith, Kerber, Astroth, & Jenkins, 2017). People who are homeless have reported feeling dehumanized in these interactions (Biederman & Nichols, 2014; Munoz, Aragon, & Fox, 2015), judged or disrespected because of their social position (Martins, 2008; McCabe, Macnee, & Anderson, 2001; Rae & Rees, 2015; Woith et al, 2017), and invisible to health care providers (Martins, 2008). Ramsay and colleagues (2019) reported that perceived prejudice by medical professionals discouraged the participants in their study from accessing health care.…”
mentioning
confidence: 99%